Gender-Based Variations in The Learning Styles of Students - prameswari, Titah Pangesti; Rahma, Tasladia Aura; Fajriyah, Viona Virza; Rahman, Hidayatur; Rahmawati, Indah Nur (Proceedings Series of Educational Studies, 2024)
This study aims to analyze the differences in learning styles (visual, auditory, kinesthetic) among seventh-grade students at SMP Negeri 3 Batu based on gender. Using a comparative research design, data was collected from 314 students through the VAK Learning Style Inventory and analyzed using chi-square tests. The findings reveal that there is no significant relationship between gender and learning styles, as indicated by an Asymp. Sig. value of 0.940. The predominant learning style among students is visual, followed by kinesthetic and auditory. These results indicate that gender does not significantly influence the learning style preferences of students. Consequently, factors such as physical, emotional, psychological, environmental, strategic, and interest-related elements play a more substantial role in shaping learning styles. The implications for educators and counselors are profound, suggesting that a broader range of influencing factors should be considered when designing interventions and support strategies to enhance student learning experiences and outcomes. Future research should investigate these variables further with larger sample sizes and consider additional factors that may impact learning styles. Keywords: learning styles; gender differences; educational interventions